Langmuir-Blodgett films as a model of the skin barrier lipids – corneocyte interface - Bernardino, Bárbara Inês Lobo Belchiorinho (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2022, Universidade de Lisboa, Faculdade de Farmácia.